INVESTIGATING THE EFFECTS OF URBAN-RURAL DISTINCTIONS AND HOUSEHOLD ECONOMIC BACKGROUNDS ON YOUNG PEOPLE’S ATTITUDES - Ezis Japar Sidik; Dhafid Wahyu Utomo (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2022)
The present study aims to investigate young people's attitudes about foreign language learning in Northern Ireland, depending on diverse residential areas and household economic backgrounds. A cross-sectional design was used in this study to conduct descriptive research. The present study uses secondary data from the Access Research Knowledge (ARK) in Northern Ireland's Young Life and Time (YLT) survey, which has been performed yearly since 2003. The survey consists of 103 items that may be completed in two ways: online (15.5 percent) or on paper (84.5 percent). The emphasis of this study was on three variables: young people's home areas (urban and rural); household economic backgrounds; and their educational backgrounds (not very well-off, average, and very well-off); and the attitude to foreign language learning. The outcomes of this study revealed that disparities between urban and rural areas had a major impact on young people's views about foreign language programs. Compared to household prosperity, which did not give strong evidence of disparities in this study, the impact of this problem was considerably more prominent.